Smallholder Farmers’ Local Knowledge in Adaptation to Climate Variability: Experience from Ludewa District, Tanzania (Tanzania Journal for Population studies and Development, 2019)
Smallholder farmers constitute a significant proportion of the world’s population that is vulnerable to climate variability. This is because they derive their livelihoods from agriculture, which heavily relies on rainfall as a source of moisture for crops production. Therefore, smallholder farmers are exposed to changes in rainfall patterns, temperature variation and extreme events such as floods and drought that could lead into disasters. Hence adaptation strategies are fundamental to reduce the impacts of climate variability. However, in order to plan for adaptation, emphasis has been on formal knowledge systems that in most cases are not accessible to and affordable by most of the smallholder farmers. Generally, farmers have their local knowledge that they use to adapt to climate variability. This article uncovers the role of smallholder farmers’ local knowledge in adaptation to climate variability. The study was conducted in Ludewa district in Njombe region. Methods used in data collection were semi-structured interviews, key informant interviews and FGDs. A total of 355 respondents were randomly selected for structured interview. The collected data were analysed using IBM Statistical Product and Service Solution, and content analysis. To reduce vulnerability to climate variability smallholder farmers use local knowledge such as weather forecasts, valley bottom cultivation, diversification of crops, early preparation of farms, and use of drought tolerant crops and diversification of economic activities and soil moisture conservation methods such as mulching. The article concludes that neither local knowledge nor formal knowledge is sufficient by its own right for sustainable adaptation. Therefore, taking action to strengthen conditions for continued use of local knowledge is essential as well as investigating on the best way to integrate with formal adaptation knowledge